MAKING APPLICATION FOR STUDENT ANIMATED PRIMARY PLANET USING MACROMEDIA FLASH 5.0 - Nur Rakhmawanti; Melani Dewi Lusita, SKom, MMSI (Jurnal Sistem Informasi, 2005)
The planet, which is part of the solar system that orbit the sun. Scientific writing isaimed to create animations Planet that can be used as medium of information for allgeneral and especially among elementary school students about the planets in theuniverse there. In scientific writing will discuss how to make a simple animationplanet is also interactive and interesting. It also included a little information about theplanet.In scientific writing, the writer uses Macromedia Flash 5.0 application program that isalready known as a maker of application program using animation and other softwaresuch as Swift 3D 2.0 to create objects with modeling and animation swf format andUlead COOL 3D 2.0 Trial to create different effects of three papers gif formatdimensions. The method used writer is by using book study that was taken fromseveral books and CDs Microsoft Encarta Encyclopedia Deluxe 2000.